Memory Activism between Values and Interests: Monuments, Museums and Institutions - Davoliūtė, Violeta; Cauvin, Thomas; Budrytė, Dovilė (Politologija, 2024)
Special Issue of Politologija Guest-edited by Violeta Davoliūtė Vilnius University Thomas Cauvin University of Luxembourg Dovilė Budrytė Georgia Gwinnett College